Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-2741
|View full text |Cite
|
Sign up to set email alerts
|

Listening with Great Expectations: An Investigation of Word Form Anticipations in Naturalistic Speech

Abstract: The event-related potential (ERP) component named phonological mismatch negativity (PMN) arises when listeners hear an unexpected word form in a spoken sentence [1]. The PMN is thought to reflect the mismatch between expected and perceived auditory speech input. In this paper, we use the PMN to test a central premise in the predictive coding framework [2], namely that the mismatch between prior expectations and sensory input is an important mechanism of perception. We test this with natural speech materials co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Yan et al (2017) discuss both Delong et al (2005) and a preprint version of Nieuwland's study and argue that the findings from this replication study can also be interpreted as in line with a prediction account; for example, the correlation between cloze values and the N400 was replicated. We interpret the combined literature (see also Wicha et al, 2004;Van Berkum et al, 2005) as supportive of anticipatory processing, especially because new evidence supporting phonological pre-activation can be found in Bentum et al (2019b); see also Poulton & Nieuwland (2022) for a critical view).…”
Section: Predictive Language Processing and The N400 Effectmentioning
confidence: 82%
“…Yan et al (2017) discuss both Delong et al (2005) and a preprint version of Nieuwland's study and argue that the findings from this replication study can also be interpreted as in line with a prediction account; for example, the correlation between cloze values and the N400 was replicated. We interpret the combined literature (see also Wicha et al, 2004;Van Berkum et al, 2005) as supportive of anticipatory processing, especially because new evidence supporting phonological pre-activation can be found in Bentum et al (2019b); see also Poulton & Nieuwland (2022) for a critical view).…”
Section: Predictive Language Processing and The N400 Effectmentioning
confidence: 82%
“…In this paper we present results showing that entropy, next to the conventional control predictors, is a useful measure in two ways: (a) as predictor in a data-oriented lmer() model, and (b) as theoretical underpinning of DIANA's choiceRT rule, and thereby closely related to the way DIANA processes the speech signal and produces dynamically changing lists of word (cohort) hypotheses. There is a close connection with the cross entropy between the two probability density functions pdf0 and pdfT which unfold over time ( [19]).…”
Section: Discussionmentioning
confidence: 99%
“…DIANA (e.g., [14]) has been used to simulate RTs in the Dutch BALDEY database [15] and the large-scale North American English data (MALD) [16], for compounds [17], to differentiate predictors in regression models [18], and for modelling the cross-entropy as a significant predictor for modeling ERP components during comprehension of continuous speech in a recent EEG experiment [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurophysiological research using the phonetic mismatch negativity (a measure of mismatch between expected and actual phonetic input) in EEG traces has shown that, from word onset onwards, listeners develop expectations about which word is uttered, based on both the bottom-up information from the acoustic signal, and the top-down expectations from the (linguistic) context [51,52]. In DIANA, the words' activations are also based on a combination of both types of evidence.…”
Section: Obtaining Activation Scores From Bottom-up and Top-down Info...mentioning
confidence: 99%